Basal Cut Prediction of a Sugarcane Culm via Numerical Simulations - Alexandre Assis Rezende Santos; Andre Luiz Gonçalves Costa; Ednilton Tavares de Andrade; Fabio Lucio Santos; Ricardo Rodrigues Magalhães (AgriEngineering)
Brazil is the world’s largest sugarcane producer, with 45.71 million tons of sugar and 29.7 billion liters of ethanol in 2023. To meet growing demand while addressing environmental concerns, sugarcane mechanical harvesting demands new research in the area. This work took into account the anisotropy and heterogeneity of sugarcane stems. Base cutting was simulated using the finite element method. For this, mechanical properties were obtained by using sugarcane common grade RB966928. The simulation was based on a rotational speed of 640 rpm and a cutting angle of 18° of the cutting blade. The results demonstrate that the cutting angle has a significant contribution to the stress level. Results found a maximum stress in the sugarcane skin around 18.2 MPa and 14.1 MPa in the sugarcane pulp. Compared to other results in the literature, the stress value difference was around 12%. Based on that, this work highlights the importance of sugarcane mechanization based on finite element analysis.